Functional Properties of Protein Isolate and Acid Soluble Protein-Rich Ingredient Co-Produced from Ethanol-Treated Industrial Rapeseed Meal - Hristo Kalaydzhiev; Petya Ivanova; Cristina L. M. Silva; Vesela I. Chalova (Polish Journal of Food and Nutrition Sciences)
Rapeseed meal is produced in large quantities as a by-product of vegetable oil production. To enhance the utility and profitability of the rapeseed meal, it was treated with ethanol and used for concomitant preparation of two protein-rich ingredients, namely protein isolate (PI) and acid soluble protein (ASP). Their functional properties were evaluated in response to two boundary concentrations of NaCl (0.03 and 0.25 mol/L) in a wide pH range (2 to 10). The PI exhibited the lowest protein solubility at isolectric point (pH 4.5) which increased both at lower and higher pH. In contrast, ASP exhibited high protein solubility (>70%) which was negligibly influenced by pH. The addition of 0.03 mol/L NaCl increased its protein solubility to almost 100% at acidic pH. The water holding capacity of PI was positively influenced by the addition of 0.25 mol/L NaCl. The ASP did not exhibit any capacity to hold water but demonstrated higher ability to absorb oil compared to the PI. Both ingredients exhibited different thermal stability in response to salt addition at pH 7 and 8. PI and ASP exhibited completely different pattern of emulsion stability as influenced by pH. While the stability of PI emulsions was close to 100% and only negligibly affected by pH, the ASP emulsion stability significantly varied in response to pH variation. The concomitant production of PI and ASP resulted in products with distinctive techno-functional properties, which makes them suitable for different applications as additives in the formulation of new food products.